Mapping Context for Social Accountability : A Resource Paper - O'Meally, Simon C. (World Bank, Washington, DC, 2014)
Demand-side governance and social accountability approaches (SAcc) have steadily gained prominence as a perceived means for achieving and improving a range of development outcomes. This resource paper focuses on the issue of SAcc and context, arising out of a growing recognition that context is critical in shaping, making, and breaking SAcc interventions. As such, the four main objectives of this paper are: to outline the main contextual factors that appear to be critical to SAcc; to examine how SAcc interventions interact with the context to bring about change in order to provide a preliminary, context-sensitive Theory of Change (ToC); to explore the operational implications that arise from first two objectives; and to offer a flexible analytical framework to guide practitioners wanting to undertake context analysis prior to engaging in demand-side activities. The paper attempted to achieve these objectives by: summarizing and building on a recently-conducted global review of the evidence-base, drawing on relevant conceptual literature to deepen understanding of SAcc and context, reviewing case-study material to extract indications of what types of SAcc approaches might work best when faced with different contextual realities, and holding consultations with experts and practitioners to test and modify the ideas being developed. The report is separated into five chapters and an annex. Chapter one introduces the topic and the rationale for undertaking work in this area. Chapter two outlines some of the key contextual variables that emerge as critical in shaping the form and effectiveness of SAcc. This provides a broad framework for understanding the important contextual constraints and opportunities. Chapter three outlines some of the key ways in which SAcc has influenced the context to produce positive change. Chapter four then explores and unpacks the practical implications of the approach. It offers two tools for SAcc practitioners to begin exploring ways to tailor to their contexts in a more structured manner. Finally, the annex, based on the paper's overall framework, provides a set of guiding questions for undertaking a context analysis prior to supporting SAcc operations.